Comparative transcriptome analysis provides insights into the distinct germination in sheepgrass (Leymus chinensis) during seed development - Li, Xiaoxia (Plant physiology and biochemistry : PPB, 2019)
Copyright © 2019. Published by Elsevier Masson SAS.